2012
DOI: 10.1371/journal.pone.0031380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Caffeine-Containing Energy Drink on Simulated Soccer Performance

Abstract: BackgroundTo investigate the effects of a caffeine-containing energy drink on soccer performance during a simulated game. A second purpose was to assess the post-exercise urine caffeine concentration derived from the energy drink intake.Methodology/Principal FindingsNineteen semiprofessional soccer players ingested 630±52 mL of a commercially available energy drink (sugar-free Red Bull®) to provide 3 mg of caffeine per kg of body mass, or a decaffeinated control drink (0 mg/kg). After sixty minutes they perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
2
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 43 publications
4
102
2
13
Order By: Relevance
“…Since then, a small number of studies have been geared to examining the effects of caffeine-containing-energy drinks on physical performance or sports tasks, mainly because of the relative novelty of these beverages [19-25,34]. Most of them have used the most popular energy drink, Red Bull®, which contains 80 mg of caffeine per 250 mL of product (one serving).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, a small number of studies have been geared to examining the effects of caffeine-containing-energy drinks on physical performance or sports tasks, mainly because of the relative novelty of these beverages [19-25,34]. Most of them have used the most popular energy drink, Red Bull®, which contains 80 mg of caffeine per 250 mL of product (one serving).…”
Section: Discussionmentioning
confidence: 99%
“…Foskett, Ali, and Gant (2009) demonstrated greater passing accuracy and VJ performance after consuming 6mg/kg BM of caffeine in a soccer simulation running and passing skill test compared with placebo. Del Coso et al (2012) demonstrated that consumption of a commercially available caffeinated sugar-free energy drink (3mg/kg BM) allowed better performance in a jump test, greater mean running speed during a RST (7 × 30m with 30sec recovery); more distance covered at a speed greater than 13km/h and a greater number of sprints during a simulated soccer game compared with placebo (p < .05). Consumption of caffeine in conjunction with carbohydrate has also been demonstrated to improve performance in physical and soccer-specific tests to a greater extent than carbohydrate alone (Gant, Ali, & Foskett, 2010;Ranchordas & Pattison, 2011).…”
Section: Ergogenic Aids: Caffeinementioning
confidence: 99%
“…A novel device comprising a 5 Hz GPS microcontroller and an interpolation algorithm that outputs positional data at a 15 Hz frequency was recently utilised to investigate the movement demands of soccer, rugby union and rugby sevens [13][15]; however, the distance measurement validity of this device has yet to be evaluated. Therefore, the aim of this study was to systematically assess the effect of rapid directional change on the distance measurement validity of a previously untested GPS device.…”
Section: Introductionmentioning
confidence: 99%